On generalized Lax equations of the Lax triple of the BKP and CKP hierarchies. Issue 2 (3rd April 2017) - Wang, Xiao-Li; Mei, Jian-Qin; Li, Min-Li; Yan, Zhao-wen
Abstract : Based on the Lax triple ( Bm, Bn, L ) of the BKP and CKP hierarchies, we derive the nonlinear evolution equations from the generalized Lax equation. The solutions of some evolution equations are presented, such as soliton and rational solutions.